2019
DOI: 10.3390/su12010181
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Footprint Estimation in a University Campus: Evaluation and Insights

Abstract: Background: The University of Talca (UT), since 2012, has been annually tracking the carbon footprint (CF) based on the Greenhouse Gas (GHG) Protocol for all its five campuses. The purpose of this paper is to illustrate the trajectory for determining the CF on campuses and identify the stressors. Methods: GHG protocol separates emissions into three scopes—1) direct; 2) indirect; 3) other indirect emissions. This study reports the emissions on the Talca campuses that are related to Scopes 1 through 3. The data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(63 citation statements)
references
References 18 publications
1
58
0
4
Order By: Relevance
“…One of the objectives of this methodology is to define parameters of comparability, not only for an installation or product over time, but on a comparative level between similar ones in such a way that it facilitates decision-making on the choice of study centers as well as contributing to the reduction in these effects. The following activity rates are proposed for weighting CF, depending on the number of users, hours of use and surface area in order to facilitate the comprehension of the client's or user's contribution to GHG emissions: kgCO 2 -e/m 2 , kgCO 2 -e/student or kgCO 2 -e/student•hour [30][31][32][33]. The use of the kgCO 2 -e per student assessment is justified as it is an objective measure for comparison and will serve as a verification ratio of the improvements adopted.…”
Section: Methodsmentioning
confidence: 99%
“…One of the objectives of this methodology is to define parameters of comparability, not only for an installation or product over time, but on a comparative level between similar ones in such a way that it facilitates decision-making on the choice of study centers as well as contributing to the reduction in these effects. The following activity rates are proposed for weighting CF, depending on the number of users, hours of use and surface area in order to facilitate the comprehension of the client's or user's contribution to GHG emissions: kgCO 2 -e/m 2 , kgCO 2 -e/student or kgCO 2 -e/student•hour [30][31][32][33]. The use of the kgCO 2 -e per student assessment is justified as it is an objective measure for comparison and will serve as a verification ratio of the improvements adopted.…”
Section: Methodsmentioning
confidence: 99%
“…For that reasons, some researchers have proposed approaches that can be used to reduce CF on campus, including through improvements in electrical energy management, (Yañez et al, 2020;Ravindran and Selvaram, 2016), the application of new renewable energy on campus (Chowdhury et al, 2018;Hasapis et al, 2017;Shukla et al, 2019) or the integration of EBT on campus (Maritz, 2019), water and waste use management (Yañez et al, 2020)., transportation (Wu et al, 2017;Liu et al, 2017;Yañez et al, 2020), building materials (Wu et al, 2017). Ravindran and Selvaram (2016), promoting greening for carbon absorption on campus (Ravindran and Selvaram, 2016), Pablo Yañez et al (2020) believe that student transportation activities on campus are a significant stressor in the problem of carbon emissions (Yañez et al, 2020). Li et al (2015) found that, on average, students produce 3.84 tons of CO2, which consists of 65% daily activities, 20% transportation, 15% academic activities (Li et al, 2015).…”
Section: Studies Of Carbon Footprint (Cf) In Universitymentioning
confidence: 99%
“…The CF calculation for the University of Indonesia recognized electricity consumption as the main emission category [31]. On the other hand, the calculation of the CF of the university campus in Chile suggested that the transportation of college students and employees to and from the campus is the main source of emissions [32]. The application of different CF calculation approaches, together with a different set of input activity data and emission factors, gave the results that were not comparable.…”
Section: Introductionmentioning
confidence: 99%